Total factor productivity growth in European stock exchanges: A non-parametric frontier approach - Heiko Schmiedel (Bank of Finland, 2002)
This paper examines progressive changes in productivity of the European stock exchange industry using non-parametric frontier techniques.Within the framework of Malmquist indices, total factor productivity growth is decomposed into technological progress and technical efficiency change for a balanced panel of all major European stock exchanges over the period 1993-1999.The principal findings indicate an overall rise in productivity over the sample period, which is driven more by technological innovation than by efficiency improvements.According to organisational setup, technological innovation is more pronounced for exchanges with the following characteristics: automation, equity and derivatives trading, for-profit governance structure, large or medium-size capitalised markets.Technological progress can be interpreted as a sign of the dynamic nature of the whole exchange industry, in which stock exchanges take advantage of intense diffusion of new cost-effective technologies and information systems to leverage themselves onto a higher production frontier.
URN:NBN:fi:bof-20140807641
Keywords: D24; G29; C23; O52; 330; stock exchanges; productivity; technological progress; Europe